2017
DOI: 10.4103/2321-0656.193997
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and clinical characteristics of a diabetic population at a tertiary care center in Assam, India

Abstract: Aims: To elucidate the sociodemographic and clinical characteristics of patients with type 2 diabetes mellitus (T2DM) attending a tertiary care hospital in Dibrugarh, Assam. Subjects and Methods: A total of 132 T2DM patients (74 males and 48 females) were included in the study. Patients were evaluated with detailed history, meticulous examination, and laboratory investigations and given a detailed interview questionnaire to fill out. Statistical Analysis Used: Graph Pad Prism, published by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
5
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 18 publications
8
5
2
Order By: Relevance
“…The classical symptoms of diabetes such as polyuria, polydipsia, and polyphagia were found in 72%, 67%, and 59%, respectively. These findings were comparable to what another study [19] found.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The classical symptoms of diabetes such as polyuria, polydipsia, and polyphagia were found in 72%, 67%, and 59%, respectively. These findings were comparable to what another study [19] found.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the highest number (40% of the study population) of type 2 DM patients belonged to the 41-50 years age group. This finding was supported by various other studies as well, supporting the fact that DM is a disease of middle-aged adults [16-19]. The female to male ratio of type 2 DM patients in our study was 1.27:1, suggesting that DM is more prevalent in females in this part of the world.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Borah M et al 21 observed that central obesity (waist circumference; men ≥ 90 and women ≥ 80 cm) was 58% in diabetic population.…”
Section: Discussionmentioning
confidence: 99%